Exploring the Backstage: Preparation and Implementation of Mass Protests in Germany. (November 2017) - Rucht, Dieter
This article aims to shed light on the understudied backstage of mass street protest preparation and implementation. In this article, I present an exploratory framework for systematizing the basic tasks and challenges of organizing a mass protest in the streets or other places. I elaborate on the concept of backstage and provide an overview of the basic tasks and challenges in preparing and organizing mass protest. These tasks are fleshed out with empirical support in the article, followed by some concluding remarks.